A study of ontogenetic level of language development and gender differences affecting language use in Acehnese language - Muhammad Aulia (Studies in English Language and Education, 2017)
There have been numerous studies analysing gender differences in language use. Most of them predominantly adopted static or hierarchical approach with obsolete understanding of gender differences. Concurrently with the high demand of socio-cultural aspects inclusion in language development studies, the research of gender in language use has also driven to the same direction with mixed talk and the use of dynamic approach as an alternative for more inclusive socio-cultural spectrum. Two student university classes were observed and their classroom conversations in mixed gender were meticulously selected for detailed analysis via N-VIVO. The study shows that social dimensions such as power, status, economy, and identity seem to be influential to Acehnese language users in mixed talks. Yet, some mixed talks are more likely to be affected by individual ontogenetic language development; the dominance of talk is relatively fading and mutual-respect is bold. Therefore, the advocacy for the dynamic approach to conducting further research in this domain is decisively important. It is also crucial for more thorough and deep analysis on the genetic language development of speakers such as their social backgrounds and study or learning experiences. This paper draws merely a minor part of a larger research project conducted in Aceh and is expected to be a trigger for future studies.